2001
DOI: 10.1359/jbmr.2001.16.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Glucocorticoid-Induced Osteoporosis with Intravenous Pamidronate and Calcium: A Prospective Controlled 1-Year Study Comparing a Single Infusion, an Infusion Given Once Every 3 Months, and Calcium Alone

Abstract: The aim of this study was to compare the action of two regimens of intravenous (iv) pamidronate in the primary prevention of glucocorticoid-induced osteoporosis (GC-OP). The primary purpose of the study was to determine whether any differences in bone mineral density (BMD) appeared after 1 year. A secondary endpoint aimed at assessing the remodeling parameters in order to better understand the mechanisms of action of the various regimens. Thirty-two patients, who required first-time, long-term glucocorticoid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(61 citation statements)
references
References 45 publications
(65 reference statements)
1
58
0
2
Order By: Relevance
“…Bisphosphonates (i.v.) proved to be effective in the treatment of postmenopausal and glucocorticoid-induced osteoporosis, 30,31 although their principal indications are hypercalcemia management in cancer patients and prevention and treatment of bone metastases of various malignancies. In our experience, zoledronic acid was the only agent, which improved bone density at cortical rich bone in hypogonadal females.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates (i.v.) proved to be effective in the treatment of postmenopausal and glucocorticoid-induced osteoporosis, 30,31 although their principal indications are hypercalcemia management in cancer patients and prevention and treatment of bone metastases of various malignancies. In our experience, zoledronic acid was the only agent, which improved bone density at cortical rich bone in hypogonadal females.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of rapid onset of fracture was not observed in two smaller studies [110,111]. Interestingly, two studies conducted in parallel under similar protocol found no differences in the risk of vertebral fractures between new and longterm CS users.…”
Section: Onset Of Skeletal Effectsmentioning
confidence: 96%
“…Proposed treatments include bisphosphonates, hormone replacement therapy, vitamin D (cholecalciferol or calciferol) and calcium, calcitriol, calcidiol, alfacalcidol, calcitonin, fluoride, testosterone, and anabolic steroids (Adachi et al 1996, Ringe et al 1999, Eastell et al 2000, Boutsen et al 2001, Å strand & Aspenberg 2002, Crandall 2002, Sambrook 2007). In addition, several alternative therapeutic approaches have been considered in recent years.…”
Section: Introductionmentioning
confidence: 99%